Development of the tourism function of rural areas of the Warmińsko-Mazurskie voivodeship in 2010 and 2020 - Brodziński, Zbigniew; Turkowski, Konrad (Economics and Environment, 2024)
Warmińsko-Mazurskie voivodeship is a characteristic region of Poland due to its natural conditions, which means that the economy is primarily agricultural and touristic. One of the main, innovative directions of non-agricultural activities supported in the rural areas of the region is rural tourism together, implemented as part of the smart specialisation "Water economy". Analysis of 19 selected indicators of tourism, tourism development and potential, as well as technical infrastructure and finances of communes, showed that in 2010 of the Warmińsko-Mazurskie voivodeship, the level of development of the tourism function of the rural areas was characterised by an average value of the synthetic Hellwig measure (0.13) and showed strong spatial heterogeneity. In 2020, under conditions of the COVID-19 pandemic, this measure decreased only slightly to a value of 0.11, primarily due to the continuation of the region's tourism development planned for the long term. The spatial arrangement of the development of the tourism function in the analysed years remained virtually unchanged. The highest values for the development of the tourism function, both in 2010 and in 2020, were recorded in municipalities located in the area of the Great Mazurian Lakes, Powiśle and the other lake districts of the region.